Adsorption behavior and mechanism of five pesticides on microplastics from agricultural polyethylene films. (April 2020) - Wang, Ting; Yu, Congcong; Chu, Qiao; Wang, Fenghe; Lan, Tao; Wang, Jingfeng
Abstract: Polyethylene (PE) agricultural soil films are easily embrittled and decomposed to microplastics (MPs) in environment. As widely used pesticides in vegetable farmland, carbendazim, dipterex, diflubenzuron, malathion, difenoconazole have potential environmental and human safety risks. They are often coexisting with MPs in the environment, and may cause consequential pollution to the ecosystem. Studying the adsorption behavior between pesticides and PE agricultural soil films MPs would be helpful for the risk assessment of co-exposure of pesticides and MPs. Herein, a systematic study on batch adsorption experiments was performed to determine the adsorption process of pesticides on MPs, the environmental factors on adsorption capacity were evaluated, and the adsorption mechanisms were discussed. Results suggested that all these five pesticides can adsorb on MPs, especially for diflubenzuron and difenoconazole. The adsorption kinetics and isotherm fitted to the Pseudo-second-order and Freundlich model, respectively, indicating that besides the adsorption onto surface sites, mass transfer and intraparticle diffusion were involved in the adsorption process, and the adsorption process was mostly controlled by physical and chemical interactions. The adsorption amounts of 5 pesticides on PE MPs follow the order of DIF > DIFE > MAL > CAR > DIP with K F correlated positively with octanol-water partition coefficients (Log K ow ). The thermodynamic study indicates the adsorption of all pesticides as spontaneous and exothermic processes. The results of this study illustrated that PE MPs can be a good carrier of pesticides in agricultural field. Graphical abstract: Image 1 Highlights: The adsorption behavior and mechanism of pesticides on PE agricultural soil films MPs were studied. The environmental factors on adsorption capacity were evaluated. Adsorption kinetics and isotherm conformed to the Pseudo-second-order and Freundlich model. The adsorption was a spontaneous and exothermic processes. MPs can adsorb and may become the source and sink of pesticides in environment.